Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/sj.ijo.0802047
|View full text |Cite
|
Sign up to set email alerts
|

Four anthropometric indices and cardiovascular risk factors in Taiwan

Abstract: OBJECTIVE:To examine the relationships between four anthropometric measurements and cardiovascular risk factors in Taiwan. DESIGN: The data was collected from four nationwide health screen centers in Taiwan from 1998 to 1999. SUBJECTS: A total of 38 556 subjects: 18 280 men and 20 276 women, mean age ¼ 37.0 AE 11.1 y. None had any known major systemic diseases or were currently on medication. MEASUREMENTS: Individual body weight, height, waist circumference (WC), and cardiovascular risk factors (blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 31 publications
4
74
0
6
Order By: Relevance
“…The present study showed that the four anthropometrics were associated with cardiovascular risk factors including hypertension, diabetes and dyslipidemia, particularly for those aged under 65 years, and this is consistent with a study in Taiwan. 20 The finding of relationship between TC and BMI was affected by age is consistent with the WHO MONICA study, where a weaker cholesterol-BMI association was found in the older age groups. 21 The findings that waist, waist hip and WHtR appeared to be more related to cardiovascular risk factors even in the old ages were consistent with other studies.…”
Section: Discussionsupporting
confidence: 88%
“…The present study showed that the four anthropometrics were associated with cardiovascular risk factors including hypertension, diabetes and dyslipidemia, particularly for those aged under 65 years, and this is consistent with a study in Taiwan. 20 The finding of relationship between TC and BMI was affected by age is consistent with the WHO MONICA study, where a weaker cholesterol-BMI association was found in the older age groups. 21 The findings that waist, waist hip and WHtR appeared to be more related to cardiovascular risk factors even in the old ages were consistent with other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Approval for analyzing the demographic and biological data in these subjects was obtained from the Ethic Committee of National Taiwan University Hospital. The anthropometric characteristics and blood pressure were measured and described previously as in Huang et al 20 A venous blood sample was taken after at least 8 h of fasting for measuring fasting plasma glucose, uric acid, triglycerides, total cholesterol and high-density lipoprotein cholesterol by an automated spectrophotometer (Toshiba TBA-200FR; Toshiba, Japan). Hepatitis B serology including antibody to hepatitis B core antigen (anti-HBc), antibody to hepatitis B surface antigen (anti-HBs) and hepatitis B surface antigen (HBsAg) was detected using chemiluminescent microparticles immunoassay (Abbott Laboratories, Wiesbaden, Germany).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The anthropometric measurements, including height, weight, waist (WC) and hip circumferences (HC), and blood pressure measurement were performed as previously described. 21 Body mass index (BMI) was calculated as weight (kg) divided by height squared (m 2 ). This study has been approved by the Ethics Committee of National Taiwan University Hospital.…”
Section: Subjects and Characterizationsmentioning
confidence: 99%
“…16,17 In addition to increasing mortality, obesity has been known to be associated with higher risk of hypertension, diabetes, dyslipidemia and CVD. [18][19][20][21] On the other hand, the main features of the syndrome cluster together more frequently than would be expected by chance alone, 1 and insulin resistance has been regarded as the basic defect leading to metabolic syndrome. [22][23][24] Taken together, these imply that a common mechanism, such as insulin resistance and/or obesity, underlies the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%